STUDI PELAKSANAAN TUGAS PENGHULU DALAM PEMBERDAYAAN MASYARAKAT DI KAMPUNG PERAWANG BARAT KECAMATAN TUALANG KABUPATEN SIAK - Ilham Firdaus; Dia Meirina Suri (UIR Press, 2019)
ABSTRACT Empowerment refers to the ability of people, especially vulnerable and weak groups, to have access to productive resources that enable them to increase their income and obtain the goods and services they need, participate in the development process and decisions that affect them, The purpose of this study are: To find out and analyze the Implementation Study of the Tasulu Task Force in Community Empowerment in Perawang Barat Village, Tualang District, Siak Regency, the indicators in this study are: Location Selection, socialization of community empowerment, Community Empowerment Process, independence of community empowerment, type of research located In the head office of Perawang Barat Village, Tualang Sub-district, Siak District, Siak District is a descriptive method with quantitative methods. Data collection techniques used are observation, questionnaires, interviews and documentation, sources of information, informa the head of the West Perawang village and the head of the West Perawang sub-district, Tualang district, Siak district. Based on the problem, basically the implementation of the tasks of the village government in community empowerment has not been effective enough because there are still many people who do not understand about the community empowerment program and there is still a lack of leaders to educate the community in Perawang Barat village, Tualang Subdistrict, Siak District. Siak regency so that it can increase its task in empowering the community to conduct socialization so that the community can understand and get results from the community empowerment program.